Stability of P50 auditory sensory gating during sleep from infancy to 4 years of age - Hunter, Sharon K. (Brain Cogn, 2015)
The stability of cerebral inhibition was assessed across early childhood using a paired-click auditory sensory gating paradigm. The P50 ERP was measured during REM (or its infant analogue, active sleep) and NREM sleep in 14 children at approximately 3 months of age and again at approximately 4 years of age. Evoked response amplitudes, latencies, and the S2/S1 ratio of the amplitudes of the evoked responses were compared between the two visits. Significant reliability was found for the S2/S1 ratio (r = .73, p = .003) during REM but not non REM sleep (r = −.05, p = .88). A significant stimulus number by sleep stage interaction (F (1,12) = 17.1, p = .001) demonstrated that the response to the second stimulus decreased during REM but not NREM sleep. These findings suggest that this measure is stable during REM sleep across early childhood, is not affected by age, and is sleep-state dependent. P50 sensory gating is a biomarker which, if used properly, may provide a mechanism to further explore changes in the developing brain or may help with early screening for psychiatric illness vulnerability.